2022
DOI: 10.3390/ijerph192113807
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Physical, Physiological, and Psychological Responses of the High-Intensity Interval (HIIT) and Small-Sided Games (SSG) Training Programs in Young Elite Soccer Players

Abstract: We investigated the effects of high-intensity interval (HIIT) and small-sided games (SSG) training programs on physiological and psychological responses in young soccer players. Twenty-four male soccer players (age 16.7 ± 0.9 years) were divided into two groups (HIIT and SSG) and completed a 6-week training programs consisting of two training sessions a week. HIIT consisted of intermittent runs lasting 15 s at the 110% maximum aerobic speed followed by a passive recovery lasting 15 s; SSG was instead structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…In the present study, mood states were negatively affected by training camp with decreased vigor scores and increased fatigue and tension scores. The POMS questionnaire is commonly used to assess athletes’ mood state [ 6 , 9 , 31 , 32 , 33 , 34 ]. During intensive training cycles, players have generally reported negative mood states [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, mood states were negatively affected by training camp with decreased vigor scores and increased fatigue and tension scores. The POMS questionnaire is commonly used to assess athletes’ mood state [ 6 , 9 , 31 , 32 , 33 , 34 ]. During intensive training cycles, players have generally reported negative mood states [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Vameval is a cardiorespiratory fitness test, performed to obtain the maximal aerobic speed (MAV; Cazorla and Léger, 1993 ). The test was performed as previously described ( Ouertatani et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of studies conducted across different stages of the season provides valuable representativeness in terms of seasonality. Within the analyzed research, studies were identified that focused exclusively on the pre-season [72,73,77], first half of the competitive season [36,70,85,86], second half of the competitive season [74,[87][88][89], and post-competitive season [37]. Additionally, some studies examined combined periods, such as pre-season and early competitive season [71,90].…”
Section: Methodological Characteristics Of Training Interventions: a ...mentioning
confidence: 99%
“…Unauthorized distribution is strictly prohibited. [69] Boraczynski et al [83] Castillo et al [74] Clemente et al [37] Dellal et al [105] Eniseler et al [90] Faude et al [70] Herazo-Sánchez et al [106] Hill-Haas et al [88] Impellizzeri et al [71] Koral et al [73] Los Arcos et al [89] Mohr et al [76] Nayiroglu et al [72] Ouertatani et al [86] Radmiminski et al [30] Safania et al [75] VO2max…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation